2016
DOI: 10.1016/j.ijsu.2016.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Urolithiasis in pregnancy

Abstract: Urolithiasis in pregnancy is a major health concern and can potentially affect the well-being of both mother and foetus. Management of this condition often entails simultaneous multidisciplinary involvement of obstetrician, radiologist and urologist. Additionally, adverse effects with usage of anaesthesia, radiation, medications and surgery on mother and foetus, limit utilisation of the full armamentarium of diagnostic and therapeutic modalities that are commonly used in non-pregnant women. This review was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
35

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 32 publications
1
28
0
35
Order By: Relevance
“…Urolithiasis during pregnancy is an important health problem that can affect the maternal and foetal health [1]. In previous studies, the incidence of urolithiasis during pregnancy has been reported to be between 1:188 and 1:4600.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urolithiasis during pregnancy is an important health problem that can affect the maternal and foetal health [1]. In previous studies, the incidence of urolithiasis during pregnancy has been reported to be between 1:188 and 1:4600.…”
Section: Introductionmentioning
confidence: 99%
“…Studies evaluating the effect of geographical location show that the incidence of urolithiasis is increasing in industrialised societies. However, there is minimal data about the role of geographical location in the incidence and prevalence of urolithiasis in pregnant women [1,2]. Urolithiasis may lead to urinary stasis, causing obstetric complications, such as preterm delivery and spontaneous abortion associated with urinary tract infection and pyelonephritis in pregnant women [3].…”
Section: Introductionmentioning
confidence: 99%
“…12 Abdominal and pelvic ultrasonography (US) are often used in young or pregnant ladies where exposure to radiation is dangerous. 13 Nowadays, computed tomography is the gold standard for diagnosis and monitoring of patients with urinary tract calculi.…”
Section: Diagnosis Of Urinary Tract Calculimentioning
confidence: 99%
“…Renal colic is one of the most common non obstetric pain and pregnancy emergencies in pregnant women [1] , and its incidence is between 1:200 and 1:2000, which could lead to severe pregnancy complications, such as abortion or premature delivery [2] . The main cause of renal colic in pregnant women contains urinary calculi, in addition to ureteral stricture, fetal ureteral obstruction and so on.…”
Section: Introductionmentioning
confidence: 99%